In situ synchrotron x-ray studies of epitaxial SrCoOx films during ionic liquid gating - Yan Li; Jill K. Wenderott; Tadesse Billo; Maoyu Wang; Alvin Chang; Hui Cao; Xi Yan; D. Bruce Buchholz; Zhenxing Feng; Hua Zhou; Supratik Guha; Dillon D. Fong (APL Materials)
The manipulation of ions in complex oxide materials can be used to mimic brain-like plasticity through changes to the resistivity of a neuromorphic device. Advances in the design of more energy efficient devices require improved understanding of how ions migrate within a material and across its interface. We investigate the exchange of oxygen and hydrogen in a model SrCoOx epitaxial film—a material that transitions between a ferromagnetic metal and antiferromagnetic insulator depending on the oxygen concentration. Changes to the film during ionic liquid gating were measured by in situ synchrotron x-ray techniques as a function of time and gate voltage, examining the reversibility of the oxide over one complete gating cycle. We find that the out-of-plane lattice constant and oxygen vacancy concentration of SrCoOx are largely reversible although changes were observed in the ordered vacancy structure. Our results provide much needed insight into electrolyte-gated phase behavior in the transition metal oxides.